Unlocking Employee Performance: The Nexus of Innovation Culture, Creativity Value, and Job Satisfaction: Menggali Kinerja Karyawan: Nexus Budaya Inovasi, Nilai Kreativitas, dan Kepuasan Kerja - Vivi Nurhaliza; Rifdah Abadiyah, SE., M.S.M., CHCM (Academia Open, 2022)
This study aims to investigate the influence of Innovation Culture and Creativity Value on Employee Performance, with Job Satisfaction as an intervening variable. A quantitative approach was employed, utilizing a probability sampling method with a simple random sampling technique to collect data from 171 employees at a leading organization. Data was collected through interviews and questionnaires, and analyzed using Partial Least Square (PLS) 3.0. The results demonstrate that both Innovation Culture and Creativity Value have a significant positive impact on Employee Performance, while Job Satisfaction plays a crucial mediating role in enhancing Employee Performance. These findings provide valuable insights for organizations seeking to foster innovation, creativity, and job satisfaction to optimize employee performance and overall organizational success. Highlights: Innovation Culture and Creativity Value positively impact Employee Performance: This study confirms that fostering an innovation culture and valuing creativity within an organization significantly enhance employee performance. Job Satisfaction mediates the relationship between Innovation Culture, Creativity Value, and Employee Performance: The findings highlight the pivotal role of job satisfaction as an intervening variable, indicating that satisfied employees are more likely to exhibit improved performance. Practical implications for organizations: The results provide practical insights for organizations to prioritize innovation, creativity, and job satisfaction as strategic drivers for optimizing employee performance and achieving overall organizational success. Keywords: Innovation Culture, Creativity Value, Job Satisfaction, Employee Performance, Quantitative Analysis